Chiral d-wave superconductivity in a triangular surface lattice mediated by long-range interaction - Cao, Xiaodong; Ayral, Thomas; Zhong, Zhicheng; Parcollet, Olivier; Manske, Dirk; Hansmann, Philipp (Physical Review B, 2018)
Adatom systems on the Si(111) surface have recently attracted an increasing attention as strongly correlated systems with a rich phase diagram. We study these materials by a single band model on the triangular lattice, including 1/r long-range interaction. Employing the recently proposed TRILEX method, we find an unconventional superconducting phase of chiral d-wave symmetry in hole-doped systems. Contrary to usual scenarios where charge and spin fluctuations are seen to compete, here the superconductivity is driven simultaneously by both charge and spin fluctuations and crucially relies on the presence of the long-range tail of the interaction. We provide an analysis of the relevant collective bosonic modes and predict how a cumulative charge and spin paring mechanism leads to superconductivity in doped silicon adatom materials.
CRIS-Team WoS Importer:2020-02-19